2015
DOI: 10.1182/blood-2014-11-612721
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of folate receptor β on acute myeloid leukemia blasts with chimeric antigen receptor–expressing T cells

Abstract: Key Points Human FRβ-specific CAR T cells target AML in vitro and in vivo without toxicity against healthy bone marrow HSCs. Combination with ATRA-mediated receptor upregulation may augment FRβ-directed CAR therapy of AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 59 publications
0
126
1
2
Order By: Relevance
“…The relationship between binding affinity and efficacy is more nuanced in the context of CARs as compared with mAbs, for which higher affinity is typically desirable. For example, on the basis of observations from preclinical studies, whereas a receptor tyrosine kinase-like orphan receptor 1 (ROR1)-CAR derived from a high-affinity scFv (with a dissociation constant of 0.56 nM) resulted in increased therapeutic index when compared with a lower-affinity variant [28][29][30] , other examples have reported that engineering the scFv for lower affinity improves the discrimination among cells with varying antigen density [31][32][33] , which could be useful for enhancing the therapeutic window for antigens differentially expressed on tumour versus normal tissues. However, this approach might increase the risk of immune evasion, owing to the emergence of low-antigen-expressing tumour cells.…”
Section: Review Articlementioning
confidence: 99%
“…The relationship between binding affinity and efficacy is more nuanced in the context of CARs as compared with mAbs, for which higher affinity is typically desirable. For example, on the basis of observations from preclinical studies, whereas a receptor tyrosine kinase-like orphan receptor 1 (ROR1)-CAR derived from a high-affinity scFv (with a dissociation constant of 0.56 nM) resulted in increased therapeutic index when compared with a lower-affinity variant [28][29][30] , other examples have reported that engineering the scFv for lower affinity improves the discrimination among cells with varying antigen density [31][32][33] , which could be useful for enhancing the therapeutic window for antigens differentially expressed on tumour versus normal tissues. However, this approach might increase the risk of immune evasion, owing to the emergence of low-antigen-expressing tumour cells.…”
Section: Review Articlementioning
confidence: 99%
“…CART generated with m909 scFv designed FRβ-specific CAR constructs resulted in more significant IFN-γ release responses when exposed to FRβ-positive AML targets than controls. These m909 CART cells proliferated, exerted potent in vitro lysis of AML cells in co-culture and demonstrated promising in vivo anti-leukemic activity [4].…”
Section: Frβ Targetingmentioning
confidence: 99%
“…СD123 также исследуется как мишень для клеточной терапии антигенным Т-клеточным ре-цептором [29]. Еще одной мишенью для Т-клеточного антигенного химерного рецептора является экспрес-сия фолатного рецептора β [30].…”
Section: перспективы оптимизации лечения острого мие-лобластного лейкозаunclassified